An Ex-situ Conservation Assessment Diversity Index (ECADI) for evaluating the coverage and diversity in germplasm collections - Sosa, Chrystian C.; Diaz, Maria Victoria; Giraldo, Norma; Mendez, Andres; Llanos, Lizeth; Ramirez Villegas, Julian (2024)
This report introduces the Ex-situ Conservation Assessment Diversity Index (ECADI), which evaluates germplasm collection diversity across four components: composition, documentation completeness, ecogeographic representativeness, and genetic usability. Using CIAT's bean, cassava, and forage collections as case studies, the ECADI framework calculates indicators for crop wild relatives and landraces to assess coverage gaps. Results highlight variability in diversity and completeness across crops and regions, identifying priority areas for improvement. Future work involves refining the methodology and expanding its application.